Fiscal Policy in Poland in the Times of Crisis - Origins and Consequences; Specyfika polityki fiskalnej w Polsce w okresie kryzysu - jej przyczyny i konsekwencje - Stefan Krajewski; Anna Krajewska (Comparative Economic Research. Central and Eastern Europe, 2011)
The present crisis has forced almost all countries to introduce an active economic policy. A lot of attention has been paid to fiscal policy and taxes in Poland. The measures taken in Poland differ considerably from global standards and decisions concerning taxes have been generally political in nature. The paper presents solutions in fiscal policy applied in Poland and explains the specificity of Poland's economy and its anti-crisis policy. – – Obecny kryzys skłonił niemal wszystkie kraje do prowadzenia aktywnej polityki gospodarczej. W USA i krajach UE duzȧ wage w pobudzaniu gospodarki przypisuje sie polityce fiskalnej i podatkom. Działania podejmowane w Polsce odbiegaja od standardoẃ sẃiatowych, a decyzje dotyczace podatkoẃ maja z reguły charakter polityczny. W artykule podjeta jest prob́a przedstawienia rozwiazanź zakresu polityki fiskalnej podejmowanych na Zachodzie oraz wyjasńienia specyfiki polskiej gospodarki i prowadzonej polityki antykryzysowej.
Keywords: 330